Chaotic Encryption Based Data Transmission Using Delta and Delta-Sigma Modulators - Günyaz Ablay (International Journal of Applied Methods in Electronics and Computers, 2016)
Delta and Delta-Sigma modulation methods have been getting a great interest recently due to the great progress in analog-digital very large scale integration technology. Since the outputs of these methods are digital, the data can be securely encrypted using very simple standard hardware. In this work, a chaotic random bit generator based approach for encrypting digital data of the delta and delta-sigma modulators is studied. The chaotic bit generation can easily be implemented in the digital hardware of the modulators due to simplicity of the chaotic dynamics.  The randomness of the generated chaotic bits are proved with visual and statistical tests. The security of the proposed approach is evaluated via key space estimation based attacks. The efficiency of the methods is validated with simulations.